METABOLIC SYNDROME AND THE RISK OF ACUTE KIDNEY DAMAGE DEVELOPMENT AFTER CORONARY ARTERY BYPASS PROCEDURE - B. G. Iskenderov; O. N. Sisina (Российский кардиологический журнал, 2015)
Aim. To find out the causal relationship of metabolic syndrome (MS) with acute kidney damage (AKD) in coronary bypass grafting patients (CABG).Material and methods.   To the clinical comparative study totally 742 patients included (489 men и 253 women) at the age 53 to 67 y. o. (mean 62,1±4,7), who underwent CABG on-pump. Of those 477 (64,3%) did not have the metabolic criteria for MS (1st group), and 265 pts. (35,7%) had MS (2nd group). Depending on the maximum increase of serum creatinine (sCr) during early post-operation period ARF was diagnosed in the 1st group on 119 patients (24,9%) in the 2nd — 92 patients (34,7%). AKD was diagnosed by AKIN.Results.   It was shown that early post operational cardiovascular complications significantly more frequently developed in AKD in both groups, and in the 2nd group comparing to the 1st. Also the procedures of hemodialysis in acute renal failure (3 stage of AKD) in the 1st group performed in 5,9% cases and in the 2nd — in 17,4% cases (p=0,015). In-hospital mortality was 2,0% to 16,3% depending on the development of AKD and MS. However in the 2nd group, in the development AKD as without this, intra-hospital mortality was significantly higher (p<0,05), than in the 1st group. It was revealed that in the case of AKD the parameters of MS were significantly higher than in its absence, especially in the 1st group. Also in the 2nd group, not related to the development of AKD metabolic parameters were higher in the 2nd group than in the 1st. Also, 1st stage and transient AKD were more prevalent in the 1st group, and III stage and non-reversible AKD with the onset of CKD — in the 2nd group. The time of hospitalization in the 2nd group was significantly longer than in the 1st (p=0,008).Conclusion. It is shown that in MS patients after CABG, comparing to those without MS, the prevalence of AKD is higher 1,5 times, in-hospital mortality — 2,5 times.